Adaptation to heat and humidity training of elite athletes in Atlanta - Burke, E.; Ryan, R.; Graham, K.; Hahn, A.; Smith, J.; Thompson, M.; Capes, M.; Telford, R. (Medicine & Science in Sports & Exercise, 1996)
Selected physiological factors associated with heat and humidity adaptation were measured in 10 well-trained middle-distance runners. This study evaluated responses of Australian athletes to the climatic conditions of Atlanta as a preparation for the 1996 Olympic Games. Tests were conducted in Australia two days prior to and post the Atlanta visit. The duration of the Atlanta exposure was 18 days. Although individual differences were observed there were no significant differences in red blood cell volume, hemoglobin, hematocrit, aldosterone, and ADH measures were noted. Implication. The adaptation of elite athletes to hot humid conditions is particularly individual. It would be incorrect to generalize adaptation procedures for groups of athletes given this variability.